Knowledge, experience and the circus: academic perspectives on the processes of communicating the environmental and health impacts of electric vehicles. Issue 6 (3rd June 2017) - Esmene, Shukru; Taylor, Timothy; Leyshon, Michael
ABSTRACT: The translation of research findings into public realms has important implications for alternative technologies, such as electric vehicles (EVs). Much existing science communication research focuses on the agency of different publics in processes of scientific knowledge uptake. This study uses research related to the environmental and health impacts of EVs as a case study to explore how the individual agency of academic researchers can influence communication. Challenges to communication and opportunities to enhance the agency of researchers to engage in public dialogue are identified, with a focus on academics at different stages of their careers. This paper proposes a new way of understanding how these individualised nuances impact the communication of a particular researcher's findings. These nuances are built through the researcher's agency; a construct of their past experiences, professional and personal relationships with other actors and previous practices of communicating to publics. Communication models have previously concentrated on the heterogeneity of other actors and publics with the huge assumption that academics work consistently, homogenously, in a neutral way to the benefit of society. EVs were chosen as an appropriate case study as they are a contemporary technology that relies on the communication of knowledge and the public understanding of this knowledge to cater for future needs. The responses elicited from the interviews highlight the individual geographies of knowledge. Hence, a reflexive understanding of their role as an individual can provide valuable insights into how a researcher may distribute knowledges more effectively in their geographies to publics